1991
DOI: 10.1007/bf00982128
|View full text |Cite
|
Sign up to set email alerts
|

Fungal volatiles: Semiochemicals for stored-product beetles (Coleoptera: Cucujidae)

Abstract: Responses by five species of cucujid grain beetles (mixed-sex adults) to various volatiles were assessed by means of a two-choice, pitfall olfactometer. The test volatiles were short-chain alcohols and ketones known to be produced by fungi. Both racemic and chiral 1-octen-3-ols were strong attractants forCryptolestes ferrugineus (Stephens), as had been found previously forOryzaephilus surinamensis (L.),O. mercator (Fauvel), andAhasverus advena (Waltl). 3-Methylbutanol was another good attractant for these four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 21 publications
0
27
0
3
Order By: Relevance
“…The parasitic fungi is specifically attracted to chemicals (unknown structures) released by its host fungal garden, as evidenced by preferential growth of the Escovopsis parasite toward their fungal host rather than to non-host fungi (Gerardo et al 2006). Fungi are known to produce volatiles that attract insects (Pierce et al 1991;Schiestl et al 2006) and/or have antimicrobial activity, e.g., penicillin. In addition, the Escovopsis strain isolated from host A will move quicker toward host A cultivar than toward other host cultivars, perpetuating Escovopsis strain and host fungal garden fidelity and the mutualism between the two fungi (Gerardo et al 2006).…”
Section: Subfamily Myrmicinaementioning
confidence: 99%
“…The parasitic fungi is specifically attracted to chemicals (unknown structures) released by its host fungal garden, as evidenced by preferential growth of the Escovopsis parasite toward their fungal host rather than to non-host fungi (Gerardo et al 2006). Fungi are known to produce volatiles that attract insects (Pierce et al 1991;Schiestl et al 2006) and/or have antimicrobial activity, e.g., penicillin. In addition, the Escovopsis strain isolated from host A will move quicker toward host A cultivar than toward other host cultivars, perpetuating Escovopsis strain and host fungal garden fidelity and the mutualism between the two fungi (Gerardo et al 2006).…”
Section: Subfamily Myrmicinaementioning
confidence: 99%
“…They have been found as aggregation pheromone components from several cucujid grain beetles (Coleoptera: Cucujidae) (Pierce et al 1991 and references therein). The 3-octanol is also a pheromone component from the mandibular glands of various species of ants, especially the genus Myrmica (Cammaerts et al 1985), while 1-octen-3-ol has been found to be a kairomone component of tsetse flies (Glossina spp.)…”
Section: Electrophysiological Responsesmentioning
confidence: 99%
“…S6; Table S2), we demonstrated that this volatile was unique to the Dracula species at our field site (see also Policha, 2014). When produced by fungi, 1-octen-3-ol and other eight-carbon compounds are known to attract both fungivorous and fungivore-predacious species (Pierce et al, 1991;Faldt et al, 1999;Combet et al, 2006), although both concentration and enantiomeric configuration seem to influence the effects on behavior (Cammaerts & Mori, 1987). Although we did not augment artificial flowers or parts with specific volatile compounds, we did account for the actual chemical phenotype of D. lafleurii by using labellum extracts rather than applying synthetic compounds.…”
Section: Researchmentioning
confidence: 99%